Simulation To Replace Clinical Hours In Nursing: An Interventional Study (Journal of Pharmaceutical Negative Results, 2023)
Technology will never replace great teachers, but in the hands of great teachers, Technology can be transformational. The study aimed to evaluate the effectiveness of simulation-based learning in terms of competency (Knowledge, skills & clinical decision making) of nursing students. Quantitative research approach with quasi experimental research design was done. Total enumerative sampling technique was used to select 405 B.Sc. (N) students from constituent colleges of nursing of MMDU Mullana. At the baseline, lecture cum discussion followed by skill sets was given by respective subject incharge on the selected medical conditions. On day 1, pre assessment of knowledge, skill through OSCE and clinical decision-making ability was conducted. Next day, students were randomly allocated to simulation group and clinical practice group by computerized random table. For the two consecutive days, intervention was administered with the help of parallel case scenarios on standardized patient/ simulators and post- test was conducted on day 15. Data was analyzed by using nonparametric test and parametric test by using SPSS 20 version. The study result showed that both simulation as well as clinical practice is effective to enhance knowledge, skills, and clinical decision-making ability of nursing students with replacement of clinical hours with simulated hours for medical surgical nursing I (15%), child health nursing (20%), mental health nursing (10%) and midwifery & obstetrical nursing (30%).